KRONİK TONSİLİTTE BAKTERİYOLOJİK ÇALIŞMA - İNCİ, Ender; ERİŞİR, Ferhat; ÖNCÜL, Oral (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Tonsillitis is one of the most common disease encountered in the community. The aim of this study was to compare the microflora at the core, anterior and posterior surfaces of the tonsils. 42 patients to whom we performed tonsillectomy for recurrent tonsillitis were entered to this study. Results.- We detected pathogen bacteria in 96% of the core swabs, whereas the surface contained frequently respiratory flora (42%). H. influenzae was isolated frequently from tonsil core swabs (94%). S. aureus was more frequently isolated from tonsil surface swabs than core swabs. Back surface of the tonsil contained bacteria that are similar to tonsil core and different from front surface. The isolated H. influenzae, S. aureus and M. catarrhalis strains are tested for beta lactamase activity. Beta lactamase activity was isolated in 29% of strains from tonsil core swabs. The most frequently isolated mixed pathogens from the core and back surface were S. aureus and H. influenzae. Conclusion.- In this article we found that the swabs from the surface of the tonsil does not represent the bacteriologic properties of the tonsil core and the value of antibiotherapy based on surface cultures.